IMPLEMENTATION STUDY: UNIVERSAL DESIGN IMPLEMENTATION IN KONGKOW PARK IN JAMBI CITY - Lubis, Elektina; Sardjono, Agung Budi (Universitas Islam Sultan Agung Semarang, 2025)
The city park serves as a public open space in urban areas where people typically release their exhaustion and boredom. Everyone in the city including people with disabilities can access this place. The government has established regulations relating to users with disabilities. All relevant parties and the people of Indonesia can use this regulation to understand the definition, meaning, and various challenges faced by users with disabilities in this country. To determine how to apply a universal design to Kongkow Park in Jambi City is the purpose of this research. The research method employs descriptive qualitative methods, guided by literature guidelines, to assess current data and identify the advantages and disadvantages of park accessibility for individuals with disabilities. The results indicate that Kongkow Park falls short of accessibility standards and universal design principles outlined in the Ministerial Regulation of Public Works and Housing No. 14 of 2017. The universal design principles state that many physical elements of the environment pose risks to people with existing disabilitiesKeywords: Accessibility, City Park, Universal Design.